Impact of Pre-Existing Comorbidities and Multimorbidities, Demography and Viral Variants on Post-Acute Sequelae of COVID-19 (‘Long COVID’) in Dutch Primary Care: A Retrospective Cohort Study - Matthijs S Berends; Maarten Homburg; Thijmen Kupers; Eline N Meijer; Isabelle Bos; Robert Verheij; Jeroen Kuiper; Marjolein Berger; Lilian Peters (Journal of Global Antimicrobial Resistance, 2024)
INTRODUCTION: Post-acute sequelae of COVID-19 (PASC), or ‘Long COVID,’ involves persistent symptoms following an acute COVID-19 infection, significantly affecting global public health. Despite extensive research, predictors and risk factors of PASC remain underexplored, necessitating comprehensive research based on objective clinical findings. This study examines PASC prevalence, associated comorbidities, demographics, and viral variants using clinical assessment of electronic healthcare records (EHR) from Dutch primary care physicians. METHODS: This retrospective cohort study utilised EHR data from 59 GP practices in northern Netherlands, encompassing 265,000 patients. Included were 19,638 patients who tested positive for COVID-19 between January 1, 2020, and December 31, 2021. PASC was identified using WHO and CDC guidelines, a Dutch pre-trained Word2Vec model, and manual clinical assessment by medical professionals. Patients were categorised based on symptom duration. The impact of pre-existing comorbidities, demographics, and viral variants on PASC was analysed using relative risk (RR) calculations and statistical tests. RESULTS: PASC prevalence was 5.8% (CI95%: 5.4-6.1%) among patients seeking primary care. Key comorbidities increasing PASC risk with statistical significance included lung disease (RR: 1.95), cardiovascular disease (RR: 1.73), diabetes (RR: 1.82), kidney disease (RR: 1.98), and mental illness (RR: 1.29). Females and individuals aged above 45 exhibited higher PASC susceptibility. CONCLUSION: Our findings underscore the significant role of chronic conditions, multimorbidity, and demographics in PASC onset and course. Enhanced awareness and targeted interventions by GPs can improve patient outcomes and mitigate PASC's long-term effects in the post-pandemic era.